An overview of aristotle and the origins of natural rights - ŞAHİN CEYLAN, ŞULE (My University, 2023)
In modern discourse, we express almost all of our legal and political demands in terms of rights. The attention the concept has received is related not only to its widespread use, but also to discussions of the nature and the functions of rights, the conditions of rights holdership, the possibility of a generic concept of rights, and so on. The discussion generally goes beyond law and legal rights. If we try to understand the essence of human rights as a special category–it is assumed that they are inalienable or indefeasible and that all human beings possess them without exception-some other questions emerge: What is the origin of the concept? Are natural rights the theoretical precursors of human rights? If so, does the tradition of natural rights go back to ancient Greece and is limited to the target of this article, the thought of Aristotle? Natural rights, and more recently human rights, are individual subjective rights that enable their holders to assert legitimate claims against others. Can we find in Aristotle’s virtue ethics a theoretical basis for equal natural rights that are inherently individual? A leading answer is given by Fred D. Miller Jr. According to him, natural rights can be based on natural justice or derived from a pre-political state of nature. The claim of natural rights theory in this second sense is that people can have moral rights prior to any social or political entity, which Aristotle would not accept since he describes human nature as a social one. Therefore, he claims that rights are not derived from human nature but from natural justice in Aristotle’s thought. In the light of Miller’s well-known article “Aristotle and the Origins of Natural Rights”, I will question the possibility of an Aristotelian concept of rights.
Keywords: Sosyal ve Beşeri Bilimler; Hukuk; Hukuk Felsefesi ve Sosyolojisi; Social Sciences and Humanities; Law; Philosophy and Sociology of Law; Sosyal Bilimler (SOC); Sosyal Bilimler Genel; HUKUK; Social Sciences (SOC); SOCIAL SCIENCES, GENERAL; LAW; Sosyal Bilimler ve Beşeri Bilimler; Social Sciences & Humanities